Electrochemical determination of sulphide at nickel electrodes in alkaline media: a new electrochemical sensor - Giovanelli, D; Lawrence, N; Jiang, L; Jones, T; Compton, R (2003)
The electrochemistry of a nickel hydroxide electrode has been studied both in the presence and absence of sulphide at microdisc and macroelectrodes. With sulphide present a new oxidative wave is observed. At a macroelectrode, this response produced a linear range from 20 to 200 μM with a corresponding limit of detection of 19μM. Under the microelectrode regime, the response was found to be linear from 20 to 200 μM with a detection limit of 10μM. The protocol has been developed into the design of a simple and cheap electrochemical sensing cell for the detection of sulphide in aqueous media. © 2002 Elsevier Science B.V. All rights reserved.